Post a New Question

Calculus

posted by .

22. Divide the expression before differentiating.

F(x) = (8x^3 - 1)/ (2x - 1)

Would the way to solve this problem be...
F(x) = [(8x^3) / (2x - 1)] - [(1)/(2x - 1)]
= [(4x^2)/(1)] - [(1) / (2x - 1)]
= (4x^2) - (2x-1)^-1

F'(x) = (8x + 1)

  • Calculus -

    No.

    The numerator is a difference of two squares, factor it, then, the denominator divides out evenly. Your answer is wrong.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question